FROM THE ELIMINATION OF SEXUAL VIOLENCE DRAFT BILL TO THE SEXUAL VIOLENCE CRIME : CONFLICT OF IDEOLOGY FEMINIST AND RELIGIOUS IDEOLOGY RELATED TO SEXUAL CONSENT - ulul albab, wildan; Evasolina Lubis; Brian Khukuh Wijaya; I Nyoman Gian Erlangga; Khairiah Aziz; Salisa (Jurnal Hukum Samudra Keadilan, 2024)
The Sexual Violence Crime Law (UU TPKS) was passed in 2022. However, the TPKS Law cannot be separated from various incidents, this is also the background for the TPKS Law taking a long time to be ratified. One of the controversial ones is related to the sexual consent paradigm which is often the reason for rejection of the TPKS Bill. This research uses the library study method, namely the author collects data by searching for data and information through books, journals, documents, articles, news and other library sources. The author will collect library data, record and analyze discourse related to sexual consent in the TPKS Bill, both within the DPR and external parties, namely community organizations. The Prosperous Justice Party (PKS), Islamic Defenders Front (FPI) and several other organizations use religious ideology in rejecting the TPKS Bill, while KUPI, Komnas Perempuan, Gusdurian, and other women's activist groups try to remember the mindset of the initial purpose of the TPKS Bill which was formed in basically departs from feminist ideology.